Validation of the Career-Related Parental Support Scale (Chinese Version). (April 2019) - Zhang, Jiahong; Chen, Gaowei; Yuen, Mantak
Our purpose in this study was to validate the existing Career-Related Parental Support Scale (CRPSS) for use with mainland Chinese students. We conducted two studies involving exploratory and confirmatory factor analyses with samples of more than 1, 000 technical education students in China. Based on the data obtained, we retained 24 out of 27 items in the original scale. We identified a bifactor model for the CRPSS (Chinese version), with a general factor of career-related parental support and four specific group factors—instrumental assistance, career-related modeling, verbal encouragement, and emotional support. Ancillary bifactor measures yielded adequate evidence of the reliability of the entire scale and each of the four subscales. We also found measurement invariance across genders, as well as gender differences in the latent variable of emotional support. Concurrent and convergent validity were supported. Implications for the use of CRPSS (Chinese version) for research and practice are suggested.